A method for preparing high-strength corrosion-resistant PPO resin-based copper-clad laminate

By impregnating and baking the electronic glass fiber cloth and hot-clad copper foil sheets on both sides of the upper and lower sides, the existing PPO resin-based copper clad plates are solved, and a high-strength, corrosion-resistant copper clad plate preparation is achieved.

CN118991210BActive Publication Date: 2025-04-08JIANG SU YAO HONG ELECTRONICS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411118645.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2025-04-08
Estimated Expiration
2044-08-15

AI Technical Summary

Technical Problem

The existing PPO resin-based copper clad plate has low structural strength and corrosion resistance, and is easily damaged by external forces or corrosive damage during use.

Method used

An electronic glass fiber cloth is used for impregnation and baking to form a semi-cured sheet, and then the copper foil sheet is hot-clad on both sides of the upper and lower sides to prepare a high-strength corrosion-resistant PPO resin-based copper clad plate.

Benefits of technology

It effectively improves the structural strength and corrosion resistance of copper clad plate, and enhances its stability in external forces and corrosion environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004994376380000081
    Figure BDA0004994376380000081
Patent Text Reader

Abstract

The invention discloses a method for preparing a high-strength, corrosion-resistant PPO resin-based copper-clad laminate, and specifically relates to the technical field of copper-clad laminates. The invention wraps a PPO resin-based impregnating material on the surface of an electronic glass fiber cloth, which can effectively ensure the structural strength and corrosion resistance of the copper-clad laminate; the increase in the polyphenylene ether content in the PPO resin-based impregnating material helps to enhance the bending strength of the copper-clad laminate, and the vinyl-terminated polyphenylene ether long chain uniformly dispersed in the cyanate resin matrix initiates a free radical reaction under the action of tert-butyl perbenzoate, and forms a semi-interpenetrating network structure with the cyanate resin, so that the bending performance of the composite material is correspondingly improved; the interpenetrating network structure formed after diallyl phthalate / polyphenylene ether and cyanate resin are cured increases the gap between molecular chains, thereby further reducing the dielectric constant and ensuring the low dielectric constant of the copper-clad laminate; the composite filler can effectively improve the corrosion resistance of the copper-clad laminate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper-clad laminates, and more specifically to a method for preparing a high-strength, corrosion-resistant PPO resin-based copper-clad laminate. Background Art

[0002] Copper clad laminate, also known as copper foil laminate, is a plate-like material made by impregnating electronic fiberglass cloth or other reinforcing materials with resin, covering one or both sides with copper foil and hot pressing. Processing, etching, drilling and copper plating are selectively performed on the copper clad laminate to make different printed circuits, thus making printed circuit boards.

[0003] Patent (CN116080211A) discloses a PPO resin-based copper-clad laminate with low dielectric loss and a preparation method thereof. First, polyphenylene ether resin is modified to enhance its solvent resistance and compatibility in the resin system. Polyphenylene ether resin, epoxy resin, modified silicon dioxide-graphene composite, solvent, curing agent, flame retardant, initiator are used to prepare glue, and glass fiber cloth is impregnated to obtain a cured sheet, the cured sheet is superimposed, the copper-clad laminate is covered, and hot pressing is performed to prepare a PPO resin-based copper-clad laminate with low dielectric loss. The PPO resin-based copper-clad laminate prepared by the method provided by the present invention has low dielectric loss and good peel strength, meeting industrial application conditions.

[0004] The PPO resin-based copper clad laminate in the above patent has low structural strength and corrosion resistance and is easily damaged by external forces or corrosion during use. Summary of the invention

[0005] In order to overcome the above-mentioned defects of the prior art, an embodiment of the present invention provides a method for preparing a high-strength, corrosion-resistant PPO resin-based copper clad laminate.

[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing a high-strength, corrosion-resistant PPO resin-based copper-clad laminate, the specific preparation steps are as follows:

[0007] Step 1: Put the electronic glass fiber cloth into the PPO resin-based impregnating material for 20 to 30 minutes, then take out the electronic glass fiber cloth, and bake it for 50 to 70 minutes to obtain a semi-cured sheet;

[0008] Step 2: Hot-press and laminate the copper foil on the upper and lower surfaces of the prepreg to obtain a high-strength, corrosion-resistant PPO resin-based copper-clad laminate.

[0009] Furthermore, in step one, the baking temperature is 170-190° C.; in step two, hot pressing is performed at 240-260° C., the pressure is 30-35 MPa, and the hot pressing time is 2-3 h.

[0010] Furthermore, in step one, the raw materials of the PPO resin-based impregnating material include, by weight percentage: 4.6-5.6% of diallyl phthalate, 1.1-1.5% of tert-butyl perbenzoate, 24.3-26.3% of polyphenylene ether, 3.6-4.6% of composite filler, and the remainder is cyanate ester resin.

[0011] Furthermore, the raw materials of the composite filler include, by weight percentage, 26.8-27.8% of dopamine hydrochloride, 4.1-4.9% of 3-aminopropyltriethoxysilane, and the remainder is hexagonal boron nitride.

[0012] Furthermore, the preparation method of the PPO resin-based impregnating material is as follows:

[0013] Step S1: weighing dopamine hydrochloride, 3-aminopropyltriethoxysilane and hexagonal boron nitride from the raw materials of diallyl phthalate, tert-butyl perbenzoate, polyphenylene ether, cyanate resin and composite filler;

[0014] Step S2: adding the dopamine hydrochloride and hexagonal boron nitride in step S1 to a buffer solution, performing ultrasonic treatment for 20 to 40 minutes, stirring at room temperature for 22 to 26 hours, and then performing vacuum filtration treatment, and performing vacuum drying treatment on the filter residue for 22 to 26 hours to obtain a base material;

[0015] Step S3: adding the base material in step S2 to an ethanol solution, then adding the 3-aminopropyltriethoxysilane in step S1, ultrasonically treating for 10 to 30 minutes, stirring in a water bath for 7 to 9 hours, centrifuging, washing, and vacuum drying for 22 to 26 hours to obtain a composite filler;

[0016] Step S4: heating the cyanate resin in step S1 to 150-160° C., stirring and reacting for 7-9 hours, and cooling to room temperature to obtain a cyanate resin prepolymer; adding the polyphenylene ether in step S1 to tetrahydrofuran, and then adding diallyl phthalate and tert-butyl perbenzoate, stirring until completely dissolved to obtain a mixture;

[0017] Step S5: Heat the cyanate resin prepolymer in step S4 to 100-110° C. to melt it and then add it to the mixed material in step S4, then add the composite filler in step S3, and then perform shearing treatment for 50-70 minutes to obtain a PPO resin-based impregnated material.

[0018] Furthermore, in step S2, the weight ratio of the total weight of dopamine hydrochloride and hexagonal boron nitride to the buffer solution is 1:(90-100), the buffer solution is a tris(hydroxymethylaminomethane) aqueous solution, the concentration of the tris(hydroxymethylaminomethane) aqueous solution is 8-12%, and the pH value of the tris(hydroxymethylaminomethane) aqueous solution is adjusted to 8.2-8.8 using a 0.08-0.12 mol / L hydrochloric acid solution to obtain a buffer solution; the ultrasonic treatment frequency is 1.3-1.7 MHz, and the ultrasonic power is 400-600 W; and the vacuum drying treatment is performed at 55-65° C.

[0019] Furthermore, in step S3, the concentration of the ethanol solution is 95-99%; the ultrasonic treatment frequency is 1.3-1.7 MHz, and the ultrasonic power is 400-600 W; the water bath temperature is 75-85° C., and the water bath stirring speed is 400-600 r / min; the centrifugal speed is 5500-6500 r / min, and the centrifugal time is 8-12 minutes; the vacuum drying treatment is carried out at 55-65° C.; in step S5, the shearing treatment speed is 4150-4250 r / min.

[0020] Furthermore, the raw materials of the PPO resin-based impregnating material include, by weight percentage, 4.6% of diallyl phthalate, 1.1% of tert-butyl perbenzoate, 24.3% of polyphenylene ether, 3.6% of composite filler, and the balance is cyanate ester resin; the raw materials of the composite filler include, by weight percentage, 26.8% of dopamine hydrochloride, 4.1% of 3-aminopropyltriethoxysilane, and the balance is hexagonal boron nitride.

[0021] Furthermore, the raw materials of the PPO resin-based impregnating material include, by weight percentage, 5.6% of diallyl phthalate, 1.5% of tert-butyl perbenzoate, 26.3% of polyphenylene ether, 4.6% of composite filler, and the balance is cyanate ester resin; the raw materials of the composite filler include, by weight percentage, 27.8% of dopamine hydrochloride, 4.9% of 3-aminopropyltriethoxysilane, and the balance is hexagonal boron nitride.

[0022] Furthermore, the raw materials of the PPO resin-based impregnating material include, by weight percentage, 5.1% of diallyl phthalate, 1.3% of tert-butyl perbenzoate, 24.8% of polyphenylene ether, 4.1% of composite filler, and the balance is cyanate ester resin; the raw materials of the composite filler include, by weight percentage, 27.3% of dopamine hydrochloride, 4.5% of 3-aminopropyltriethoxysilane, and the balance is hexagonal boron nitride.

[0023] Technical effects and advantages of the present invention:

[0024] 1. The method of the present invention is used to put the electronic glass fiber cloth into the PPO resin-based impregnating material for impregnation and baking treatment to obtain a semi-cured sheet, and the PPO resin-based impregnating material is wrapped on the surface of the electronic glass fiber cloth, which can effectively ensure the structural strength and corrosion resistance of the copper clad laminate; the copper foil is hot-pressed and laminated on the upper and lower surfaces of the semi-cured sheet to obtain a high-strength and corrosion-resistant PPO resin-based copper clad laminate; dopamine hydrochloride and hexagonal boron nitride are added to a buffer solution, ultrasonically treated, and stirred at room temperature for reaction, which can effectively ensure that the dopamine hydrochloride undergoes a polymerization reaction to form polydopamine, and the polydopamine is wrapped on the surface of the hexagonal boron nitride, vacuum filtration treatment is performed, and the filter residue is vacuum dried to obtain dry polydopamine-modified hexagonal boron nitride; the dry polydopamine-modified hexagonal boron nitride is added to an ethanol solution, and then 3-aminopropyltriethoxysilane is added for ultrasonic treatment, and a water bath stirring treatment is performed, which can effectively ensure that the polydopamine and 3- Aminopropyl triethoxysilane is reacted to prepare 3-aminopropyl triethoxysilane for surface modification of hexagonal boron nitride coated with polydopamine; cyanate resin is made into cyanate resin prepolymer, which can effectively improve the rapid contact reaction of cyanate resin prepolymer in subsequent processes; polyphenylene ether is added into tetrahydrofuran for dissolution, and then diallyl phthalate and tert-butyl perbenzoate are added, and stirred until completely dissolved, which can effectively ensure the rapid blending of polyphenylene ether, diallyl phthalate and tert-butyl perbenzoate, and ensure the subsequent reaction with cyanate resin prepolymer; the cyanate resin prepolymer is heated and melted, and then added into the mixture, and sheared for 60 minutes to obtain a PPO resin-based impregnating material, which can effectively ensure the rapid blending of polyphenylene ether, diallyl phthalate, tert-butyl perbenzoate and cyanate resin prepolymer, and facilitate the uniformity and stability of the internal structure of the subsequent semi-cured sheet and copper clad laminate;

[0025] 2. In the present invention, the addition of diallyl phthalate can increase the fluidity of the PPO resin-based impregnating material and improve the processing difficulty; under the initiation of tert-butyl perbenzoate, diallyl phthalate and the vinyl group of polyphenylene ether can undergo free radical polymerization, and the vinyl group of polyphenylene ether has a certain promoting effect on the curing of cyanate ester resin. There are a large number of benzene ring structures in polyphenylene ether, and the cyanate ester resin can form a heat-resistant triazine ring structure after curing, which can effectively ensure the heat resistance of the copper clad laminate; the increase in the content of polyphenylene ether helps to enhance the bending strength of the copper clad laminate The vinyl-terminated polyphenylene ether long chains uniformly dispersed in the cyanate ester resin matrix initiate free radical reactions under the action of tert-butyl perbenzoate, reducing the crosslinking density of the triazine ring and forming a semi-interpenetrating network structure with the cyanate ester resin, thereby improving the bending properties of the composite material accordingly; diallyl phthalate, as an active plasticizer, has good compatibility with polyphenylene ether and can further improve the mechanical properties of the system when added in small amounts; the interpenetrating network structure formed after the curing of diallyl phthalate / polyphenylene ether and cyanate ester resin increases the gap between the molecular chains , thereby further reducing the dielectric constant and ensuring the low dielectric constant of the copper clad laminate; the hexagonal boron nitride in the composite filler can effectively improve the corrosion resistance of the copper clad laminate, and dopamine hydrochloride is polymerized to form polydopamine with the assistance of a weak alkaline buffer. At the same time, the hexagonal boron nitride is non-covalently coated by utilizing the π-π interaction between polydopamine and hexagonal boron nitride, and polydopamine is wrapped on the surface of hexagonal boron nitride, which can effectively modify the hexagonal boron nitride; according to the different charge characteristics of polydopamine at different pH values, 3-aminopropyltriethoxysilane is electrostatically assembled, and polydopamine Polydopamine was successfully coated on the surface of hexagonal boron nitride, and 3-aminopropyltriethoxysilane was attached to the hexagonal boron nitride coated with polydopamine through electrostatic assembly. With the addition of 3-aminopropyltriethoxysilane, a film was coated on the hexagonal boron nitride coated with polydopamine, so that the excellent adhesion of hexagonal boron nitride to polydopamine and the improved compatibility of 3-aminopropyltriethoxysilane composite filler in PPO resin-based impregnating material made the dispersion effect of hexagonal boron nitride in PPO resin-based impregnating material better, further improving the corrosion resistance of copper clad laminate. DETAILED DESCRIPTION

[0026] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Embodiment 1:

[0028] The present invention provides a method for preparing a high-strength, corrosion-resistant PPO resin-based copper-clad laminate, and the specific preparation steps are as follows:

[0029] Step 1: Put the electronic glass fiber cloth into the PPO resin-based impregnating material for 25 minutes, then take out the electronic glass fiber cloth, and bake it at 180°C for 60 minutes to obtain a prepreg;

[0030] The raw materials of the PPO resin-based impregnating material include, by weight percentage, 4.6% of diallyl phthalate, 1.1% of tert-butyl perbenzoate, 24.3% of polyphenylene ether, 3.6% of composite filler, and the balance is cyanate ester resin; the raw materials of the composite filler include, by weight percentage, 26.8% of dopamine hydrochloride, 4.1% of 3-aminopropyltriethoxysilane, and the balance is hexagonal boron nitride;

[0031] The preparation method of the PPO resin-based impregnating material is as follows:

[0032] Step S1: weighing dopamine hydrochloride, 3-aminopropyltriethoxysilane and hexagonal boron nitride from the raw materials of diallyl phthalate, tert-butyl perbenzoate, polyphenylene ether, cyanate resin and composite filler;

[0033] Step S2: adding the dopamine hydrochloride and hexagonal boron nitride in step S1 into a buffer solution, performing ultrasonic treatment for 30 minutes, stirring at room temperature for 24 hours, and then performing vacuum filtration treatment, and performing vacuum drying treatment on the filter residue for 24 hours to obtain a base material;

[0034] Step S3: adding the base material in step S2 to an ethanol solution, and then adding 3-aminopropyltriethoxysilane in step S1, ultrasonically treating for 20 minutes, stirring in a water bath for 8 hours, centrifuging, washing, and vacuum drying for 24 hours to obtain a composite filler;

[0035] Step S4: heating the cyanate resin in step S1 to 155° C. and stirring for reaction for 8 hours, and cooling to room temperature to obtain a cyanate resin prepolymer; adding the polyphenylene ether in step S1 to tetrahydrofuran, and then adding diallyl phthalate and tert-butyl perbenzoate, stirring until completely dissolved, to obtain a mixture;

[0036] Step S5: heating the cyanate resin prepolymer in step S4 to 105° C. to melt it and then adding it to the mixed material in step S4, then adding the composite filler in step S3, and then performing shearing treatment for 60 minutes to obtain a PPO resin-based impregnated material;

[0037] Step 2: hot-press and laminate the copper foil on the upper and lower surfaces of the prepreg: hot-press and mold at 250°C, with a pressure of 32MPa and a hot-pressing time of 2.5h; obtain a high-strength, corrosion-resistant PPO resin-based copper-clad laminate;

[0038] The weight ratio of the total weight of dopamine hydrochloride and hexagonal boron nitride to the buffer solution in step S2 is 1:90, the buffer solution is a tris(hydroxymethyl)aminomethane aqueous solution, the concentration of the tris(hydroxymethyl)aminomethane aqueous solution is 8%, and the pH value of the tris(hydroxymethyl)aminomethane aqueous solution is adjusted to 8.2 using a 0.08 mol / L hydrochloric acid solution to obtain a buffer solution; the ultrasonic treatment frequency is 1.3 MHz, and the ultrasonic power is 400 W; vacuum drying treatment is performed at 55° C.; the concentration of the ethanol solution in step S3 is 95-99%; the ultrasonic treatment frequency is 1.3 MHz, and the ultrasonic power is 400 W; the water bath temperature is 75° C., and the water bath stirring speed is 400 r / min; the centrifugal speed is 5500 r / min, and the centrifugal time is 8 minutes; vacuum drying treatment is performed at 55° C.; in step S5, the shearing treatment speed is 4150 r / min.

[0039] Embodiment 2:

[0040] Different from Example 1, the raw materials of the PPO resin-based impregnating material include, by weight percentage, 5.6% of diallyl phthalate, 1.5% of tert-butyl perbenzoate, 26.3% of polyphenylene ether, 4.6% of composite filler, and the balance is cyanate ester resin; the raw materials of the composite filler include, by weight percentage, 27.8% of dopamine hydrochloride, 4.9% of 3-aminopropyltriethoxysilane, and the balance is hexagonal boron nitride.

[0041] Embodiment 3:

[0042] Different from Examples 1-2, the raw materials of the PPO resin-based impregnating material include, by weight percentage, 5.1% of diallyl phthalate, 1.3% of tert-butyl perbenzoate, 24.8% of polyphenylene ether, 4.1% of composite filler, and the balance is cyanate ester resin; the raw materials of the composite filler include, by weight percentage, 27.3% of dopamine hydrochloride, 4.5% of 3-aminopropyltriethoxysilane, and the balance is hexagonal boron nitride.

[0043] Embodiment 4:

[0044] The difference from Example 3 is that in step S2, the weight ratio of the total weight of dopamine hydrochloride and hexagonal boron nitride to the buffer solution is 1:100, the buffer solution is a tris(hydroxymethylaminomethane) aqueous solution, the concentration of the tris(hydroxymethylaminomethane) aqueous solution is 12%, and the pH value of the tris(hydroxymethylaminomethane) aqueous solution is adjusted to 8.8 using a 0.12 mol / L hydrochloric acid solution to obtain a buffer solution; the ultrasonic treatment frequency is 1.7 MHz, and the ultrasonic power is 600 W; vacuum drying is performed at 65°C; the concentration of the ethanol solution in step S3 is 99%; the ultrasonic treatment frequency is 1.7 MHz, and the ultrasonic power is 600 W; the water bath temperature is 85°C, and the water bath stirring speed is 600 r / min; the centrifugal speed is 6500 r / min, and the centrifugal time is 12 minutes; vacuum drying is performed at 65°C; in step S5, the shearing treatment speed is 4250 r / min.

[0045] Embodiment 5:

[0046] The difference from Example 3 is that in step S2, the weight ratio of the total weight of dopamine hydrochloride and hexagonal boron nitride to the buffer solution is 1:95, the buffer solution is a tris(hydroxymethylaminomethane) aqueous solution, the concentration of the tris(hydroxymethylaminomethane) aqueous solution is 10%, and the pH value of the tris(hydroxymethylaminomethane) aqueous solution is adjusted to 8.5 using a 0.10 mol / L hydrochloric acid solution to obtain a buffer solution; the ultrasonic treatment frequency is 1.5 MHz, and the ultrasonic power is 500 W; vacuum drying is performed at 60°C; the ethanol solution concentration in step S3 is 98%; the ultrasonic treatment frequency is 1.5 MHz, and the ultrasonic power is 500 W; the water bath temperature is 80°C, and the water bath stirring speed is 500 r / min; the centrifugal speed is 6000 r / min, and the centrifugal time is 10 minutes; vacuum drying is performed at 60°C; in step S5, the shearing treatment speed is 4200 r / min.

[0047] Comparative Example 1:

[0048] Different from Example 5, in a method for preparing a high-strength, corrosion-resistant PPO resin-based copper-clad laminate,

[0049] The raw materials of the PPO resin-based impregnating material include, by weight percentage, 1.3% of tert-butyl perbenzoate, 24.8% of polyphenylene ether, 4.1% of composite filler, and the balance is cyanate resin; the raw materials of the composite filler include, by weight percentage, 27.3% of dopamine hydrochloride, 4.5% of 3-aminopropyltriethoxysilane, and the balance is hexagonal boron nitride.

[0050] Comparative Example 2:

[0051] Different from Example 5, in a method for preparing a high-strength, corrosion-resistant PPO resin-based copper-clad laminate,

[0052] The raw materials of the PPO resin-based impregnating material include, by weight percentage, 5.1% of diallyl phthalate, 1.3% of tert-butyl perbenzoate, 24.8% of polyphenylene ether, 4.1% of composite filler, and the balance is cyanate ester resin; the raw materials of the composite filler include, by weight percentage, 4.5% of 3-aminopropyltriethoxysilane, and the balance is hexagonal boron nitride.

[0053] Comparative Example 3:

[0054] Different from Example 5, in a method for preparing a high-strength, corrosion-resistant PPO resin-based copper-clad laminate,

[0055] The preparation method of the PPO resin-based impregnating material is as follows:

[0056] Step S1: weighing dopamine hydrochloride, 3-aminopropyltriethoxysilane and hexagonal boron nitride from the raw materials of diallyl phthalate, tert-butyl perbenzoate, polyphenylene ether, cyanate resin and composite filler;

[0057] Step S2: adding the dopamine hydrochloride, hexagonal boron nitride and 3-aminopropyltriethoxysilane in step S1 into a buffer solution, performing ultrasonic treatment for 30 minutes, stirring at room temperature for 24 hours, and then performing vacuum filtration treatment, and performing vacuum drying treatment on the filter residue for 24 hours to obtain a composite filler;

[0058] Step S3: heating the cyanate resin in step S1 to 155° C. and stirring for reaction for 8 hours, and cooling to room temperature to obtain a cyanate resin prepolymer; adding the polyphenylene ether in step S1 to tetrahydrofuran, and then adding diallyl phthalate and tert-butyl perbenzoate, stirring until completely dissolved, to obtain a mixture;

[0059] Step S4: heating the cyanate resin prepolymer in step S3 to 105° C. to melt it and then adding it to the mixed material in step S3, then adding the composite filler in step S2, and then performing shearing treatment for 60 minutes to obtain a PPO resin-based impregnated material;

[0060] In step S2, the weight ratio of the total weight of dopamine hydrochloride and hexagonal boron nitride to the buffer solution is 1:95, the buffer solution is a tris(hydroxymethylaminomethane) aqueous solution, the concentration of the tris(hydroxymethylaminomethane) aqueous solution is 10%, and the pH value of the tris(hydroxymethylaminomethane) aqueous solution is adjusted to 8.5 using a 0.10 mol / L hydrochloric acid solution to obtain a buffer solution; the ultrasonic treatment frequency is 1.5 MHz, and the ultrasonic power is 500 W; vacuum drying treatment is performed at 60° C.; in step S4, the shear treatment speed is 4200 r / min.

[0061] In the above embodiments and comparative examples, diallyl phthalate was purchased from Shanghai Chuangsai Technology Co., Ltd., with the article number Dr-C1616900; tert-butyl perbenzoate was purchased from Wuhan Kanos Technology Co., Ltd., with the article number 8598479; polyphenylene ether was purchased from Nantong Xingchen Synthetic Materials Co., Ltd., with the model number LXN050; cyanate ester resin was purchased from bisphenol A cyanate ester resin monomer of Xinyi Yongcheng Chemical Co., Ltd., with the article number 001; dopamine hydrochloride was purchased from Hubei Yongkuo Technology Co., Ltd., with the article number YK3229; 3-aminopropyltriethoxysilane was purchased from Hubei Wande Chemical Co., Ltd., with the article number WD1140; hexagonal boron nitride was purchased from Wuhan Prov Biotechnology Co., Ltd., with the article number 0002; and trishydroxymethylaminomethane was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., with the article number T110599.

[0062] The high-strength and corrosion-resistant PPO resin-based copper-clad laminates in the above-mentioned Examples 1-5 and Comparative Examples 1-3 were respectively tested, and the high-strength and corrosion-resistant PPO resin-based copper-clad laminates were tested for bending strength (tested according to GB / T 1449-2005 standard) and hydrochloric acid resistance degradation rate. The test results are shown in Table 1:

[0063] Table 1:

[0064]

[0065] As shown in Table 1, in the present invention, the addition of diallyl phthalate can increase the fluidity of the PPO resin-based impregnating material and improve the processing difficulty; under the initiation of tert-butyl perbenzoate, diallyl phthalate and the vinyl groups carried by polyphenyl ether can undergo free radical polymerization, and the vinyl groups carried by polyphenyl ether have a certain promoting effect on the curing of cyanate ester resin. There are a large number of benzene ring structures in polyphenyl ether, and the cyanate ester resin can form a heat-resistant triazine ring structure after curing, which can effectively ensure the heat resistance of the copper clad laminate; the increase in the content of polyphenyl ether is helpful to enhance the bending strength of the copper clad laminate, and the vinyl-terminated polyphenyl ether long chains uniformly dispersed in the cyanate ester resin matrix initiate free radical reactions under the action of tert-butyl perbenzoate, thereby reducing the crosslinking density of the triazine ring and reacting with the cyanate ester resin. The resin forms a semi-interpenetrating network structure, which improves the bending performance of the composite material accordingly; diallyl phthalate, as an active plasticizer, has good compatibility with polyphenylene ether. When added in small amounts, it can further improve the mechanical properties of the system; cyanate ester resin forms a highly symmetrical triazine ring network structure when cured, which is insensitive to polarization relaxation under the action of an external electric field, so it has a lower dielectric constant and dielectric loss; after adding polyphenylene ether, a large number of benzene ring structures are introduced, and there are no strong polar groups, so the dielectric constant is further reduced; the interpenetrating network structure formed after diallyl phthalate / polyphenylene ether and cyanate ester resin are cured increases the gap between molecular chains, thereby further reducing the dielectric constant and ensuring the low dielectric constant of the copper clad laminate; the composite filler can be used for PPO Filler treatment of the resin-based impregnating material can further improve the performance of the PPO resin-based impregnating material; the hexagonal boron nitride in the composite filler can effectively improve the corrosion resistance of the copper-clad laminate; dopamine hydrochloride is polymerized to form polydopamine with the assistance of a weak alkaline buffer solution; at the same time, the hexagonal boron nitride is non-covalently coated by utilizing the π-π interaction between polydopamine and hexagonal boron nitride, and polydopamine is wrapped on the surface of hexagonal boron nitride, which can effectively modify the hexagonal boron nitride; 3-aminopropyltriethoxysilane is electrostatically assembled according to the different charge characteristics of polydopamine at different pH values, and polydopamine is successfully coated on the surface of hexagonal boron nitride. 3-aminopropyltriethoxysilane is attached to the hexagonal boron nitride wrapped with polydopamine through electrostatic assembly. The addition of 3-aminopropyltriethoxysilane forms a film on the hexagonal boron nitride wrapped with polydopamine, so that the excellent adhesion of the hexagonal boron nitride to polydopamine and the improved compatibility of the composite filler in the PPO resin-based impregnating material by 3-aminopropyltriethoxysilane make the hexagonal boron nitride dispersed in the PPO resin-based impregnating material better, and further improve the corrosion resistance of the copper clad laminate; in step one, the electronic glass fiber cloth is placed in the PPO resin-based impregnating material for impregnation and baking to obtain a semi-cured sheet, and the PPO resin-based impregnating material is wrapped on the surface of the electronic glass fiber cloth, which can effectively ensure the structural strength and corrosion resistance of the copper clad laminate; in step two, the copper foil is hot-pressed and laminated on the upper and lower surfaces of the semi-cured sheet to obtain a high-strength and corrosion-resistant PPO resin-based copper clad laminate;In step S2, dopamine hydrochloride and hexagonal boron nitride are added to a buffer solution, ultrasonically treated, and stirred at room temperature for reaction, which can effectively ensure that dopamine hydrochloride undergoes a polymerization reaction to form polydopamine, and polydopamine is wrapped on the surface of hexagonal boron nitride, vacuum filtration is performed, and the filter residue is vacuum dried to obtain dry polydopamine-modified hexagonal boron nitride; in step S3, the dry polydopamine-modified hexagonal boron nitride is added to an ethanol solution, and 3-aminopropyltriethoxysilane is added for ultrasonic treatment, and stirred in a water bath, which can effectively ensure that polydopamine and 3-aminopropyltriethoxysilane react, and 3-aminopropyltriethoxysilane is prepared to perform surface modification treatment on the hexagonal boron nitride wrapped with polydopamine; in step S4, cyanic acid is added to the ethanol solution, and 3-aminopropyltriethoxysilane is added for ultrasonic treatment, and stirred in a water bath, which can effectively ensure that polydopamine and 3-aminopropyltriethoxysilane react, and 3-aminopropyltriethoxysilane is prepared to perform surface modification treatment on the hexagonal boron nitride modified by polydopamine; The cyanate resin is made into a cyanate resin prepolymer, which can effectively improve the rapid contact reaction of the cyanate resin prepolymer in the subsequent process; polyphenylene ether is added to tetrahydrofuran for dissolution, and then diallyl phthalate and tert-butyl perbenzoate are added and stirred until completely dissolved, which can effectively ensure the rapid blending of polyphenylene ether, diallyl phthalate and tert-butyl perbenzoate, and ensure the subsequent reaction with the cyanate resin prepolymer; in step S5, the cyanate resin prepolymer is heated and melted and then added to the mixture, and sheared for 60 minutes to obtain a PPO resin-based impregnating material, which can effectively ensure the rapid blending of polyphenylene ether, diallyl phthalate, tert-butyl perbenzoate and cyanate resin prepolymer, and facilitate the uniformity and stability of the internal structure of the subsequent prepreg and copper clad laminate. ;

[0066] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-strength, corrosion-resistant PPO resin-based copper-clad laminate, characterized in that: The specific preparation steps are as follows: Step 1: Put the electronic glass fiber cloth into the PPO resin-based impregnating material for 20 to 30 minutes, then take out the electronic glass fiber cloth, and bake it for 50 to 70 minutes to obtain a semi-cured sheet; Step 2: hot-pressing and laminating the copper foil on the upper and lower surfaces of the prepreg to obtain a high-strength, corrosion-resistant PPO resin-based copper-clad laminate; In step 1, the raw materials of the PPO resin-based impregnating material include, by weight percentage, 4.6-5.6% of diallyl phthalate, 1.1-1.5% of tert-butyl perbenzoate, 24.3-26.3% of polyphenylene ether, 3.6-4.6% of composite filler, and the balance is cyanate ester resin; the raw materials of the composite filler include, by weight percentage, 26.8-27.8% of dopamine hydrochloride, 4.1-4.9% of 3-aminopropyltriethoxysilane, and the balance is hexagonal boron nitride; the preparation method of the PPO resin-based impregnating material is as follows: Step S1: weighing dopamine hydrochloride, 3-aminopropyltriethoxysilane and hexagonal boron nitride from the raw materials of diallyl phthalate, tert-butyl perbenzoate, polyphenylene ether, cyanate resin and composite filler; Step S2: adding the dopamine hydrochloride and hexagonal boron nitride in step S1 to a buffer solution, performing ultrasonic treatment for 20 to 40 minutes, stirring at room temperature for 22 to 26 hours, and then performing vacuum filtration treatment, and performing vacuum drying treatment on the filter residue for 22 to 26 hours to obtain a base material; Step S3: adding the base material in step S2 to an ethanol solution, then adding the 3-aminopropyltriethoxysilane in step S1, ultrasonically treating for 10 to 30 minutes, stirring in a water bath for 7 to 9 hours, centrifuging, washing, and vacuum drying for 22 to 26 hours to obtain a composite filler; Step S4: heating the cyanate resin in step S1 to 150-160° C., stirring and reacting for 7-9 hours, and cooling to room temperature to obtain a cyanate resin prepolymer; adding the polyphenylene ether in step S1 to tetrahydrofuran, and then adding diallyl phthalate and tert-butyl perbenzoate, stirring until completely dissolved to obtain a mixture; Step S5: Heat the cyanate resin prepolymer in step S4 to 100-110° C. to melt it and then add it to the mixed material in step S4, then add the composite filler in step S3, and then perform shearing treatment for 50-70 minutes to obtain a PPO resin-based impregnated material.

2. The method for preparing a high-strength, corrosion-resistant PPO resin-based copper-clad laminate according to claim 1, characterized in that: In step one, the baking temperature is 170-190° C., and in step two, hot pressing is performed at 240-260° C., the pressure is 30-35 MPa, and the hot pressing time is 2-3 hours.

3. The method for preparing a high-strength, corrosion-resistant PPO resin-based copper-clad laminate according to claim 1, characterized in that: The weight ratio of the total weight of dopamine hydrochloride and hexagonal boron nitride to the buffer solution in step S2 is 1:(90-100), the buffer solution is a tris(hydroxymethylaminomethane) aqueous solution, the concentration of the tris(hydroxymethylaminomethane) aqueous solution is 8-12%, and the pH value of the tris(hydroxymethylaminomethane) aqueous solution is adjusted to 8.2-8.8 using a 0.08-0.12 mol / L hydrochloric acid solution to obtain a buffer solution; the ultrasonic treatment frequency is 1.3-1.7 MHz, and the ultrasonic power is 400-600 W; and the vacuum drying treatment is performed at 55-65° C.

4. The method for preparing a high-strength, corrosion-resistant PPO resin-based copper-clad laminate according to claim 1, characterized in that: In step S3, the concentration of the ethanol solution is 95-99%; the ultrasonic treatment frequency is 1.3-1.7 MHz, and the ultrasonic power is 400-600 W; the water bath temperature is 75-85° C., and the water bath stirring speed is 400-600 r / min; the centrifugal speed is 5500-6500 r / min, and the centrifugal time is 8-12 minutes; the vacuum drying treatment is carried out at 55-65° C.; in step S5, the shearing treatment speed is 4150-4250 r / min.

5. The method for preparing a high-strength, corrosion-resistant PPO resin-based copper-clad laminate according to claim 1, characterized in that: The raw materials of the PPO resin-based impregnating material include, by weight percentage, 4.6% of diallyl phthalate, 1.1% of tert-butyl perbenzoate, 24.3% of polyphenylene ether, 3.6% of composite filler, and the balance is cyanate ester resin; the raw materials of the composite filler include, by weight percentage, 26.8% of dopamine hydrochloride, 4.1% of 3-aminopropyltriethoxysilane, and the balance is hexagonal boron nitride.

6. The method for preparing a high-strength, corrosion-resistant PPO resin-based copper-clad laminate according to claim 1, characterized in that: The raw materials of the PPO resin-based impregnating material include, by weight percentage, 5.6% of diallyl phthalate, 1.5% of tert-butyl perbenzoate, 26.3% of polyphenylene ether, 4.6% of composite filler, and the balance is cyanate ester resin; the raw materials of the composite filler include, by weight percentage, 27.8% of dopamine hydrochloride, 4.9% of 3-aminopropyltriethoxysilane, and the balance is hexagonal boron nitride.

7. The method for preparing a high-strength, corrosion-resistant PPO resin-based copper-clad laminate according to claim 1, characterized in that: The raw materials of the PPO resin-based impregnating material include, by weight percentage, 5.1% of diallyl phthalate, 1.3% of tert-butyl perbenzoate, 24.8% of polyphenylene ether, 4.1% of composite filler, and the balance is cyanate ester resin; the raw materials of the composite filler include, by weight percentage, 27.3% of dopamine hydrochloride, 4.5% of 3-aminopropyltriethoxysilane, and the balance is hexagonal boron nitride.

Citation Information

Patent Citations

  • PPO resin-based copper-clad plate with low dielectric loss and preparation method thereof

    CN116080211A

  • Thermosetting resin composition and copper clad laminate for high-speed base plate, and preparation of copper clad laminate

    CN110776739A

  • Anti-aging corrosion-resistant battery backboard and preparation method thereof

    CN115558345A

  • Polyphenyl ether-based polymer composite material as well as preparation method and application thereof

    CN115612276A